2021
DOI: 10.1007/s11113-021-09646-7
|View full text |Cite
|
Sign up to set email alerts
|

Using Synthetic Adjustments and Controlling to Improve County Population Forecasts from the Hamilton–Perry Method

Abstract: Tayman and Swanson (J Popul Res 34(3):209–231, 2017) found in Washington State counties that a forecast based on the Hamilton–Perry method using a synthetic adjustment (SYN) of cohort change ratios and child-woman ratios had greater accuracy and less bias compared to forecasts holding these ratios constant (CONST). In this paper, we assess the robustness of SYN’s efficacy by evaluating forecast accuracy, bias, and distributional error across age groups in counties nationwide. We also investigate whether foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous research has shown how constraining projections to more aggregate independent projections can improve forecast accuracy [5] , [6] , [7] , [8] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Previous research has shown how constraining projections to more aggregate independent projections can improve forecast accuracy [5] , [6] , [7] , [8] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%